Characterization of essential oil from red citronella leaves (Cymbopogon nardus L.) - Wicaksono, Akhmad Permadi; Afandi, Fadila Ardiansyah; Wira, Guardiola Rosa; Adzani, Mayla Fayzza; Erliyanti, Nove Kartika (Konversi, 2024)
Citronella leaves are generally processed using conventional methods to obtain its essential oil. UMAE (Ultrasound-Microwave Assisted Extraction) method can be a replacement of conventional methods. UMAE is an extraction process assisted by ultrasonic waves and microwaves. NaCl solution can be used as a solvent in the UMAE method due to its large dielectric constant value. This research aimed to examinethe effect of microwave power and salt concentration on the characteristics of citronella leaf essential oil (density, refractive index, color, and solubility in alcohol). The extraction method used in this research was Ultrasound Microwave-Assisted Extraction (UMAE). The solvent and material used in this research were NaCl salt solution and Red Citronella Leaves (Cymbopogon nardus L.). The first stage carried out in this research was pre-treatment assisted by ultrasonic waves for five minutes at a temperature of 35 ᵒC, solvent concentrations of 0, 2, 4, 6, and 8% (w/v). The second stage was microwave-assisted extraction with a microwave power of 150, 300, 450, 600, and 750 Watts. The best results were produced at a concentration of 4% NaCl salt solution and 450Watt microwave power with yellow color, density value 0.8898 g/mL, refractive index 1.456, and solubility in alcohol 1:2. Overall, the quality of citronella leaves essential oil was in range of SNI 06-3953 1995. Therefore, the Red Citronella Leaves (Cymbopogon nardus L.) in the future can be considered as the alternative resource of citronella essential oil due to its good characteristics, among many varieties of citronella plants.